Tomographic and histologic aspects in patients with pancreas exocrine neoplasm - Vivian Dosouto Lemus; Maria do Rosario Monteiro Soares; Yaima Lemus Dosouto; Ivelisa Flores Ramírez; José Daniel García Fajardo (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The pancreas cancer originates in the pancreatic gland and it is one of the more invasive neoplasms due to its quick dissemination, lack of specific symptoms in its beginnings and its late diagnosis. Objective: To characterize patients with pancreas cancer according to variables of interest. Methods: An observational, descriptive and cross-sectional study was carried out in the Imaging Service of Saturnino Lora Teaching Provincial Clinical Surgical Hospital in Santiago de Cuba, from January, 2013 to December, 2017 to 70 patients with suggestive tomographic diagnosis of this malignancy. Results: In the series the pancreatic exocrine tumor prevailed in patients older than 60 years (37.1 %), the male sex (54.2 %) and mixed race (61.4 %). The predominant histologic diagnosis was the ductal adenocarcinoma hardly differentiated (47.2 %), as long as, the risk factors mostly associated with the neoplasm were fatty foods (68.6 %), nicotine addiction (61.4 %) and alcoholism (50.0 %), and the most frequent personal pathological history was diabetes mellitus (37.1 %). Conclusions: The computerized axial tomography provides a detailed description of the pancreatic neoplasms and their extension, which is very useful for the staging of these malignancies and, also, it determines the therapeutic behavior we should follow.